GENDER PERFORMATIVITY AND MANIPULATION IN GILLIAN FLYNN’S GONE GIRL - Michelle Arletta; Rahayu Puji Haryanti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This research analyzes Gillian Flynn’s Gone Girl (2012) to explore the construction of gender identity through manipulation in modern marriage. Marriage is presented not merely as a personal relationship, but as an institution shaped by social expectations and gender norms. This study examines manipulation not only as a behavioral tendency, but also as a form of gender performativity through which femininity may be strategically enacted within a patriarchal context. The research employs a qualitative method using two types of data: primary and secondary. The primary data source is Flynn’s novel, while the secondary data consist of journals, articles, and other relevant references. Drawing on Judith Butler’s theory of gender performativity, the study suggests that gender performance can function as a means of negotiating power within intimate relationships rather than merely as a repeated social practice. The findings reveal that marriage in the novel frequently operates as a social performance, in which maintaining appearances becomes more important than the relationship itself. When this performance can no longer be sustained, conflict emerges, and manipulation becomes a strategic mechanism for negotiating control and public legitimacy. Thus, manipulation is effective because gender performance has already been socially accepted and normalized. Furthermore, the findings indicate that modern marriage can be understood as a space in which gender identity is continuously shaped and negotiated through social expectations and relational dynamics, suggesting that women are not merely passive participants, but also possess agency to influence and control the direction of the relationship.